2014
DOI: 10.1089/jwh.2014.4742
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Gail Model and Breast Cancer Preventive Therapy Among Three Primary Care Specialties

Abstract: An overall minority of providers, most notably in FM and IM, use the Gail model to assess, and chemoprevention to decrease, breast cancer risk. Until providers are more consistent in their use of the Gail model (or other breast cancer risk calculator) and chemoprevention, opportunities to intervene in women at increased risk will likely continue to be missed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
50
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 34 publications
2
50
2
Order By: Relevance
“…A cross-sectional, web-based survey of physicians [16] revealed that only 13 % of providers had recommended or prescribed preventive therapy (8 % family medicine, 9 % internal medicine, 30 % gynecology).…”
Section: Physicians’ Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…A cross-sectional, web-based survey of physicians [16] revealed that only 13 % of providers had recommended or prescribed preventive therapy (8 % family medicine, 9 % internal medicine, 30 % gynecology).…”
Section: Physicians’ Barriersmentioning
confidence: 99%
“…Most PCPs have never used the Gail model [20], which is currently the best available tool to identify suitable candidates for preventive therapy [16, 17]. In a cross-sectional survey of 300 PCPs, only 37 and 33 % of internists and family physicians, respectively, reported ever using the Gail model, as compared to 60 % of gynecologists [16]. …”
Section: Physicians’ Barriersmentioning
confidence: 99%
“…However, only 40% of primary care providers (n ¼ 316) in a recent cross-sectional, web-based survey reported using the Gail model to assess breast cancer risk and even fewer (13%) reported recommending or prescribing chemoprevention medications (Corbelli et al, 2014); a lack of provider familiarity with both risk assessment and the benefits and risks or chemoprevention options were identified as barriers to chemoprevention uptake (Corbelli et al, 2014;Reimers & Crew, 2012). Continuing education to enhance provider skill evaluating and in communicating information about risk to patients as well as awareness of and comfort prescribing chemoprevention medications is therefore of paramount importance.…”
Section: Implications For Practice And/or Policymentioning
confidence: 99%
“…Characteristics of Mammography Patients Reporting Female and Male versusMale-Only Sexual Partners, 2013-2014 …”
mentioning
confidence: 99%
“…82 Different medical specialties vary widely in their use of the Gail model (33–37% for internal medicine and family medicine compared to 60% for gynecology) and ever prescribing anti-estrogens (8–9% for internal medicine and family medicine compared to 30% for gynecology). 83 Additional barriers to routine breast cancer risk assessment include time constraints, lack of familiarity and comfort prescribing preventive therapy. 84 Physician recommendation and effective communication strongly influence uptake of preventive therapy for breast cancer.…”
Section: Introductionmentioning
confidence: 99%